Estudio retrospectivo de la actividad física del adulto mayor de la parroquia Vilcabamba y su incidencia en la calidad de vida actual período 2013-2014 - Picoita Malla, Fausto Aníba (2015)
This research addresses the issue of "RETROSPECTIVE STUDY OF PHYSICAL ACTIVITY OF SENIOR ADULT VILCABAMBA PARISH AND ITS IMPACT ON THE QUALITY OF LIFE CURRENT PERIOD 2013-2014"; having reference to the following specific objectives: Identify physical activities that older adults performed the Vilcabamba parish in his youth, and meet the current physical condition of the elderly Vilcabamba the same that would aid the parish physical and intellectual development. The methods used were the inductive-deductive that allowed me to understand the feature of very high intellectual conscience, since based on the interpretations, could get to the facts that lead us to the truth of the events; analytical method allowed me; socialize the process or processes involved in implementing a context that must inter-act the proposal. The instruments used were the survey of a sample of 50 adults over Vilcabamba and a physical test that allowed me to know the status of the current Physical State seniors Vilcabamba. The results of the surveys and the physical test applied, allowed me to pass the hypotheses in my research to be positive; and conclude that physical activities in their youth, helped maintain his fitness at present and therefore a better quality of life.